Partnering for Cutoff Wall Project Success - Matteo Bertoni; Aem Ragy; Osvaldo Valdez (Deep Foundations Institute, 2023)
The East St. Louis Deep Cutoff Wall project is located in the area of East St. Louis, Illinois, across the Mississippi River from the city of St. Louis, Missouri, along the left descending bank of the river. The project is a fundamental part of the U.S. Army Corps of Engineers' (USACE) effort to rehabilitate and secure the aging East St. Louis levee system that provides flood protection to approxi- mately 250,000 residents and more than $4.5 billion in economic value. The project was devised and de- signed by USACE as a cutoff wall to be installed in the Metro East Sanitary District levee segment, one of the levee segments that form the East St. Louis system. The contract for the construc- tion of the cutoff wall was awarded in November 2019 to Bauer Foundation, the American subsidiary of the Bauer Group.